An Introduction to Ibn al-Haytham's Contributions to the Field of Optics - Muhammad Taqiyuddin; Alhafidh Nasution (Indonesian Journal of Islamization Studies, 2025)
The work of Muslim scientists has always attracted attention. Uniquely, the work became widespread and known through its critics, the majority of whom were orientalists. Here are the historians in the field of science. One of the favorite Muslim scientists to study his work is Ibn al-Haitsam. This study with this model of literature seeks to specifically reveal some aspects of optics developed by Ibn Haitsam after the introduction of Islam with previous civilizations. The data revealed focuses on Ibn Haitsam's literature obtained from oriental studies; which specifically discusses optics. This study finds that various works of Ibn Haitsam that have been edited, commented on, and translated by orientalists have a high level of complexity. Therefore, it is necessary to be given a structured advance in understanding it. Moreover, with a concise purpose; namely to know the role of Ibn Haitsam from one of the branches of his various works, namely Optics. The results of the critical analysis say, that Ibn Haitsam's scientific ethos is so high. Because, he honestly acknowledges that his knowledge can evolve through the contributions of previous scientists. Even further, he reached a critical level of study and revised his previous views on the concept of human vision.